Associations between biochemical components of human semen with seminal conditions. (4th March 2019) - Collodel, Giulia; Nerucci, Fabiola; Signorini, Cinzia; Iacoponi, Francesca; Moretti, Elena
ABSTRACT: The aim of the study was to assess whether abnormal levels of seminal biochemical components could be associated with semen alterations and infertility. In this study, 92 human ejaculates from selected men were analyzed. Albumin, estradiol, ferritin, total proteins (TP), folic acid (FA), vitamin B12, alkaline phosphatase (ALP), creatine kinase (CK), gamma-glutamyl transpeptidase (GGT), lactate dehydrogenase were evaluated. Semen parameters and biochemical components of the 92 samples were correlated bySpearman's rho coefficient. Albumin showed a negative correlation with sperm progressive motility and vitality (P < 0.05), CK with sperm concentration and vitality (P < 0.05), ferritin with sperm morphology (P < 0.05). FA negatively correlated with sperm concentration (P < 0.05) and GGT with sperm motility (P < 0.05). The values of biochemical components were compared for each semen parameters (concentration, motility, morphology, vitality) in samples ≤5th percentile with those >5th percentile and in patients with/without leukocytospermia, presence/absence of germ cells, increased/normal viscosity by Mann Whitney U test. The albumin (P < 0.001) and TP (P < 0.05) levels and the GGT activity (P < 0.001) were significantly higher in patients with sperm motility ≤5th percentile. Patients with sperm vitality ≤5th percentile showed increased albumin concentration (P < 0.01) and the CK activity (P < 0.001). The presence of germ cells in semen was concomitant with high values of ferritin (P < 0.01); the ALP activity (P < 0.01) and FA level (P < 0.001) were decreased in hyperviscous semen. The FA and estradiol levels were significantly decreased in the smoker group compared to those measured in the non-smoker group. Subjects were grouped in infertile patients and men with unknown reproductive potential. Infertile patients albumin and ferritin were significantly increased (P < 0.05). This study suggests that some biochemical components may be associated with human seminal pathological conditions. Abbreviations : ALP: alkaline phosphatase; LDH: lactate dehydrogenase; GGT: γ-glutamyl transferase; CK: creatine kinase; ACP: acid phosphatase; ALB: albumin; TP: total proteins; FERR: ferritin, E: estradiol; FOL: folic acid; B12: vitamin B12; FSH: follicle stimulating hormone; LH: luteinizing hormone; T: testosterone; BMI: body mass index; WHO: World Health Organization.